Epilepsy Seizures in Spontaneously Hypertensive Rats After Acoustic Stimulation: Role of Renin–Angiotensin System - Becari, Christiane; Pereira, Giorgia Lemes; Oliveira, José A. C.; Polonis, Katarzyna; Garcia-Cairasco, Norberto; Costa-Neto, Claudio M.; Pereira, Marilia G. A. G. (Frontiers in Neuroscience, 2020)
Hypertension is a common comorbidity observed in individuals with epilepsy. Growing evidence suggests that lower blood pressure is associated with reduced frequency and severity of seizures. In this study, we sought to investigate whether the renin–angiotensin system (RAS), which is a critical regulator of blood pressure, is involved in the pathogenesis of audiogenic epilepsy-related seizures in a hypertensive rat model. Spontaneously hypertensive rats (SHRs) were given RAS inhibitors, angiotensin-converting enzyme (ACE) inhibitor or angiotensin II type I receptor (AT1R) antagonist, for 7 days prior to inducing epileptic seizures by acoustic stimulation. After the pretreatment phase, blood pressure (BP) of SHRs normalized as expected, and there was no difference in systolic and diastolic BP between the pretreated SHRs and normotensive rat group (Wistar). Next, treated and untreated SHRs (a high BP control) were individually subjected to acoustic stimuli twice a day for 2 weeks. The severity of tonic–clonic seizures and the severity of temporal lobe epilepsy seizures (product of forebrain recruitment) were evaluated by the mesencephalic severity index (Rossetti et al. scale) and the limbic index (Racine’s scale), respectively. Seizures were observed in both untreated (a high BP control) SHRs and in SHRs treated with AT1R antagonist and ACE inhibitor. There was no statistical difference in the mesencephalic severity and limbic index between these groups. Our results demonstrate that SHRs present seizure susceptibility with acoustic stimulation. Moreover, although RAS inhibitors effectively reduce blood pressure in SHR, they do not prevent developing epileptic seizures upon acoustic stimulation in SHR. In conclusion, our study shows that RAS is an unlikely link between hypertension and susceptibility to epileptic seizures induced by acoustic stimulation in SHRs, which is in contrast with the anticonvulsant effect of losartan in other animal models of epilepsy.